A Sociological Review of Law Against the Exploitation of Street Children by Parents in the City of Yogyakarta - Vicki Dwi Purnomo; Kelik Endro Suryono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aims are to find out what are the factors that influence the exploitation of street children by parents in the city of Makassar, to find out how the government's efforts to prevent and resolve acts of exploitation of street children by parents in the city of Yogyakarta. This qualitative study uses research methods to produce descriptive data. The research location is located in the city of Yogyakarta. Data collection was carried out using observation, interviews and documentation techniques. The results of the study show that there are 4 factors behind the exploitation of street children by parents in the city of Makassar, namely: economic factors (poverty), environmental factors, and cultural factors. The research results are expected to provide benefits and contributions to scientific thinking and add new knowledge to authors, to provide useful information about street children in the city of Yogyakarta and further research is needed.